Th2/1 Hybrid Cells Occurring in Murine and Human Strongyloidiasis Share Effector Functions of Th1 Cells - Bock, Cristin N.; Babu, Subash; Breloer, Minka; Rajamanickam, Anuradha; Boothra, Yukhti; Brunn, Marie-Luise; Kühl, Anja A.; Merle, Roswitha; Löhning, Max; Hartmann, Susanne; Rausch, Sebastian (Frontiers in Cellular and Infection Microbiology, 2017)
Infections by the soil-transmitted threadworm Strongyloides stercoralis affect 30–100 million people worldwide, predominantly in tropic and sub-tropic regions. Here we assessed the T helper cell phenotypes in threadworm-infected patients and experimental murine infections with focus on CD4+ T cells co-expressing markers of Th2 and Th1 differentiation. We show that mice infected with the close relative S. ratti generate strong Th2 responses characterized by the expansion of CD4+ GATA-3+ cells expressing IL-4/-5/-13 in blood, spleen, gut-draining lymph nodes, lung and gut tissue. In addition to conventional Th2 cells, significantly increased frequencies of GATA-3+T-bet+ Th2/1-hybrid cells were detected in all organs and co-expressed Th2- and Th1-cytokines at intermediate levels. Assessing the phenotype of blood-derived CD4+ T cells from South Indian patients infected with S. stercoralis and local uninfected control donors we found that GATA-3 expressing Th2 cells were significantly increased in the patient cohort, coinciding with elevated eosinophil and IgE/IgG4 levels. A fraction of IL-4+CD4+ T cells simultaneously expressed IFN-γ hence displaying a Th2/1 hybrid phenotype. In accordance with murine Th2/1 cells, human Th2/1 cells expressed intermediate levels of Th2 cytokines. Contrasting their murine counterparts, human Th2/1 hybrids were marked by high levels of IFN-γ and rather low GATA-3 expression. Assessing the effector function of murine Th2/1 cells in vitro we found that Th2/1 cells were qualified for driving the classical activation of macrophages. Furthermore, Th2/1 cells shared innate, cytokine-driven effector functions with Th1 cells. Hence, the key findings of our study are that T helper cells with combined characteristics of Th2 and Th1 cells are integral to immune responses of helminth-infected mice, but also occur in helminth-infected humans and we suggest that Th2/1 cells are poised for the instruction of balanced immune responses during nematode infections.